Simulation model of active distribution network lines with high proportion distributed photovoltaic energy storage access - Zhai, Di; Ye, Wenhua; Ma, Ming; Deng, Yunshu; Yang, Jingchen (Center of Biomass & Renewable Energy (CBIORE), 2025)
To address the voltage stability and power quality issues prevalent in active distribution lines with a significant proportion of distributed PV energy storage, the study proposes a novel multi-time reconfiguration loss reduction model for active distribution networks. This model employs a phased optimization strategy and a security-constrained optimal tidal current technique to enhance efficiency and reliability. The proposed method can effectively allocate reactive power output based on reactive power capacity, achieving better reactive voltage control. The nodes with a smaller reactive power capacity, nodes 2 and 3, exhibited an output of 0.33 Mvar. In comparison, the nodes with a medium capacity, nodes 27 and 28, demonstrated an output of 0.71 Mvar. Finally, the nodes with the largest capacity, nodes 16 and 17, exhibited an output of up to 0.98 Mvar. This differentiated reactive power allocation strategy effectively optimized voltage control and ensured the stability of active distribution network lines. In addition, the annual system operating cost of the suggested method was reduced by 167,889.33 yuan. From this, the proposed method demonstrates significant benefits in both economic and environmental aspects. It provides a practical and feasible optimization strategy for the high proportion of distributed photovoltaic energy storage connected to active distribution networks, which can promote the transformation of energy structure.